2009
DOI: 10.1111/j.1365-2184.2008.00571.x
|View full text |Cite
|
Sign up to set email alerts
|

Continuous hypoxic culturing maintains activation of Notch and allows long‐term propagation of human embryonic stem cells without spontaneous differentiation

Abstract: Our data, thus, indicate that hypoxic exposure has the capacity to sustain long-term self-renewal of hESCs and that this effect is mediated through activation of Notch.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
84
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(92 citation statements)
references
References 33 publications
8
84
0
Order By: Relevance
“…Embryo culture in atmospheric oxygen (20%), compared to physiological concentrations, is associated with perturbed gene expression (Harvey et al 2004, Rinaudo et al 2006 changes to the proteome (Katz-Jaffe et al 2005), alterations in metabolic activity (Lane & Gardner 2005, Wale & Gardner 2012, Wale & Gardner 2013) and retarded development in several species, including the human (Thompson et al 1990, Meintjes et al 2009, Waldenströ m et al 2009). In previous reports, hES cell lines showed changes in metabolism (Forristal et al 2013, Harvey et al 2014, epigenetics (Petruzzelli et al 2014), transcription (Forsyth et al 2008, Westfall et al 2008, self-renewal capacity (Prasad et al 2009), clonal recovery , Hewitt et al 2006 and pluripotency (Ezashi et al 2005) in response to changes in environmental oxygen concentration. For example, culture of hES cells in physiological oxygen (w5%) results in increased glucose consumption and increased lactate production when compared to cells cultured in 20% oxygen (Forristal et al 2013, Harvey et al 2014, Turner et al 2014.…”
Section: Introductionmentioning
confidence: 85%
“…Embryo culture in atmospheric oxygen (20%), compared to physiological concentrations, is associated with perturbed gene expression (Harvey et al 2004, Rinaudo et al 2006 changes to the proteome (Katz-Jaffe et al 2005), alterations in metabolic activity (Lane & Gardner 2005, Wale & Gardner 2012, Wale & Gardner 2013) and retarded development in several species, including the human (Thompson et al 1990, Meintjes et al 2009, Waldenströ m et al 2009). In previous reports, hES cell lines showed changes in metabolism (Forristal et al 2013, Harvey et al 2014, epigenetics (Petruzzelli et al 2014), transcription (Forsyth et al 2008, Westfall et al 2008, self-renewal capacity (Prasad et al 2009), clonal recovery , Hewitt et al 2006 and pluripotency (Ezashi et al 2005) in response to changes in environmental oxygen concentration. For example, culture of hES cells in physiological oxygen (w5%) results in increased glucose consumption and increased lactate production when compared to cells cultured in 20% oxygen (Forristal et al 2013, Harvey et al 2014, Turner et al 2014.…”
Section: Introductionmentioning
confidence: 85%
“…Also, culturing human ESCs by constant hypoxic conditions may maintain pluripotency by sustaining Notch activation (67). Recent research data also show that using hypoxic conditions (5% O 2 ) increases the efficiency of generation of iPSCs from mouse MEFs using OCT3/4, Sox2, and Klf4 retroviral transduction, as well as with nonviral vectors, such as plasmid expression vectors or piggyback transposition system (99).…”
Section: Role Of Hypoxia In Pluripotent Stem Cellsmentioning
confidence: 99%
“…It has been demonstrated that NICD-dependent transcriptional activity, and thus the stem cell pluripotency, may be regulated by oxygen partial tension (11). It is interesting to note that several previous studies confirmed that pericellular oxygen concentration has an effect on hESCs self-renewal and differentiation (12,13). In the case of hematopoietic stem cells that reside in a relatively hypoxic niche, it has previously been shown that activation of Notch blocked differentiation and resulted in T cell acute lymphoblastic leukemia (14).…”
Section: Introductionmentioning
confidence: 95%